2015
DOI: 10.1159/000380902
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis Impairs the Human Microcirculation Independent from Macrohemodynamic Parameters

Abstract: Hemodynamic changes during haemodialysis are common. Often these changes are associated with symptoms that are thought to be the result of reduced microcirculatory blood flow and oxygen delivery. The microcirculatory effect of hemodialysis is scarcely researched, though of possible influence on patient outcome. New techniques have become available to visualise and analyse microvascular blood flow. We performed an observational study using Sidestream Dark Field imaging, a microscopic technique using polarised l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Recent developments, notably Sidestream Dark Field imaging, a microscopic technique using polarised light to visualise erythrocytes passing through sublingual capillaries, have enabled the direct visualization of the microcirculation during HD and observed a decline in perfused vessel density during HD. This was not related to changes in blood pressure, showing that microcirculatory changes can occur, which are unnoticed by changes in macrovascular parameters [34]. …”
Section: Effects Of Dialysis On Tissue Perfusionmentioning
confidence: 99%
“…Recent developments, notably Sidestream Dark Field imaging, a microscopic technique using polarised light to visualise erythrocytes passing through sublingual capillaries, have enabled the direct visualization of the microcirculation during HD and observed a decline in perfused vessel density during HD. This was not related to changes in blood pressure, showing that microcirculatory changes can occur, which are unnoticed by changes in macrovascular parameters [34]. …”
Section: Effects Of Dialysis On Tissue Perfusionmentioning
confidence: 99%
“…Although most microcirculatory measurements using HVM were carried out in the sublingual area, several investigations of the microcirculation were carried out directly on organ surfaces during surgery [2,[11][12][13][14][15]. Indeed, sublingual microcirculatory alterations have been identified using HVM in a wide range of disease states other than sepsis and shock [16][17][18][19][20][21][22][23][24][25][26] and in different age groups including critically ill newborns [27]. In 2009, an international multicenter observational prevalence study in intensive care patients involving 36 ICUs worldwide enrolling 501 patients identified microcirculatory alterations (microvascular flow index, MFI < 2.6) in combination with tachycardia (heart rate > 90) as an independent risk factor for increased hospital mortality [28].…”
Section: Introductionmentioning
confidence: 99%
“…This can occur as a consequence of the nature of the disease or due to an ineffective therapy such fluids [45,46] or vasopressors not being effective in improving the microcirculation [47][48][49]. Such a loss of coherence between the macro-and microcirculation has been described in several clinical and experimental studies [8,23,44,[48][49][50][51][52] and has been found to be an independent predictor of adverse outcome and organ dysfunction [6-10]. Its manifestation, however, is a dynamic process depending on the interactions between disease, therapy, and time.…”
Section: Introductionmentioning
confidence: 99%
“…They found a significant reduction in microvascular flow after ultrafiltration, which could be attenuated by placing patients in the Trendelenberg position, suggesting that the effect was due to relative volume status rather than capillary dysfunction. Another small study confirmed that the density and proportion of perfused vessels fell significantly over hemodialysis, and that microvascular dysfunction was not reflected in blood pressure or arterial saturations . A third study was only able to replicate the findings of reduced sublingual perfusion in patients undergoing rapid isolated ultrafiltration, perhaps due to differences in baseline volume status …”
Section: What Happens To Cellular Oxygen Delivery During Hemodialysis?mentioning
confidence: 95%
“…Another small study confirmed that the density and proportion of perfused vessels fell significantly over hemodialysis, and that microvascular dysfunction was not reflected in blood pressure or arterial saturations. 34 A third study was only able to replicate the findings of reduced sublingual perfusion in patients undergoing rapid isolated ultrafiltration, perhaps due to differences in baseline volume status. 35 Videomicroscopy techniques, including laser Doppler of microvessels, have also been applied to the skin during hemodialysis.…”
Section: Tissue Perfusionmentioning
confidence: 98%